2013
DOI: 10.1177/0961203313485828
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus associated with moyamoya syndrome: a case report and literature review

Abstract: Moyamoya syndrome (MMS) is a rare, chronic progressive cerebrovascular occlusive disease that is characterized by a stenosis or occlusion of the bilateral internal carotid arteries and the circle of Willis arteries leading to the development of collateral vessels as visualized by cerebral angiography. We report a case of a 24-year-old woman with nephrotic syndrome whose biopsy showed membranous nephropathy. Ten months after the diagnosis she suffered sudden right hemiplegia and seizure. She was diagnosed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…Moyamoya disease presenting concurrently with other specific autoimmune diseases has also been described in the literature. 2,8,9,13,16,19,23 In this study, autoimmune thyroid diseases, all other autoimmune diseases, and other comorbidities tended to have higher prevalence rates in unilateral MMD patients than in bilateral MMD patients. Nevertheless, no significant differences were observed between unilateral and bilateral MMD with regard to each specific concurrent autoimmune disease, including GD, HT, Type 1 diabetes mellitus, and all other evaluated autoimmune diseases.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Moyamoya disease presenting concurrently with other specific autoimmune diseases has also been described in the literature. 2,8,9,13,16,19,23 In this study, autoimmune thyroid diseases, all other autoimmune diseases, and other comorbidities tended to have higher prevalence rates in unilateral MMD patients than in bilateral MMD patients. Nevertheless, no significant differences were observed between unilateral and bilateral MMD with regard to each specific concurrent autoimmune disease, including GD, HT, Type 1 diabetes mellitus, and all other evaluated autoimmune diseases.…”
Section: Discussionmentioning
confidence: 51%
“…Additionally, the authors of these studies hypothesized that there is a potential autoimmune component to the pathogenesis of moyamoya vasculopathy. 2,13,[15][16][17]19,23 In this study, we found that unilateral MMD may be more likely to be associated with autoimmune disease than bilateral MMD. Moreover, these findings suggest that unilateral MMD may be more frequently observed with autoimmune comorbidities.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…In cases associated with SLE and MMD, many hypotheses and analyses indicate that MMD aggravation is correlated with disease activity; one case suggests that cessation of immunosuppressive therapy may result in the development of MMD [12]. If BD has a disease pattern similar to SLE, increased disease activity related to stressful events such as psychiatric stress could aggravate MMD.…”
Section: Discussionmentioning
confidence: 99%